Interpersonal Communication to Manage Dating Trauma Feelings - Desneildawati, Devy; Budi Lestari, SU, Dr. Dra. Sri (Interaksi Online, 2016)
It has been human’s fundamental need to socialize with others, including to have romantic relationship. Romantic relationship is one of important processes in adulthood phase. In early adulthood (college period), choosing romantic partner is more future-oriented, which is a marriage. In reality, not all of romantic relationship go without flaws. As the result of severe conflict situation is discontinuation of romantic relationship which can leads to trauma. Discontinuation of a romantic relationship that involved two individuals will surely leaving wounds both physically, psychologically, and socially. Anxiety is one of psychologic trauma symptoms toward mistakes and unpleasant incident from previous relationship. This is a qualitative-descriptive kind of research, using phenomenological approach with interpretative-constructivism paradigm, focusing on communication for managing romantic relationship trauma. Research informants are couples who getting back together with their ex and individuals who choose to find new partner domiciled in Semarang and Jakarta. Based on Interpersonal Communication Develops and Sustain Relationships, Committed Relationships Theory, Mediated Interpersonal Communication Theory, Attachment Theory, Maintenance Relationships Theory, and Coordinated Management of Meaning Theory, which could explain much about managing romantic relationship trauma. As the result, communication to managing the trauma conducted intensively and effectively. The process of managing trauma must be done with identification and acceptance to any cause that ends the relationship. Women feel bigger trauma than men, as well as openness toward partner. Interest and dependence toward partner become factors that cause ‘move on phase’. Reminiscing sweet moment, past and experience challenge, shared meanings, shared future, commitment, culture, sacrifice, environment, parents, and friends have a role to make decision after managing trauma. Secure attachment could becomes preoccupied attachment and vice versa. There are two different decision after having trauma which are getting back to ex partner and looking for a new partner.